Laparoscopic greater curvature plication as a stomach sparing gastric sleeve: is it a worthy weight losing procedure for morbid obesity? - Abdallah, Adel M.; El Nemr, Mohamed E. (International Surgery Journal, 2018)
Background: Although laparoscopic sleeve gastrectomy (SLG) considered a gold standard way of management of morbid obesity, it still has serious complications as bleeding and staple line leak. Laparoscopic greater curvature plication (LGCP) was introduced as a trial gastric restrictive procedure and recently modified and standardized to obtain a gastric sleeve without resection and hence lower complications rates with the advantage of being a reversible procedure. Methods: 28 patients suffered from morbid obesity with body mass indices less than 50 kg/m2 filling the selection criteria of the study were prepared for Stomach Sparing Gastric Sleeve (SSGS). After devascularization of the greater curvature, double in-folding of the greater curvature using non-absorbable 2-0 sutures starting at the angle of His to 3-4 cm proximal to the pylorus, were done. Results: 28 patients with preoperative mean total body weight (TBW) of 118.7±15.5 kg and a mean BMI of 38±6.5 kg/m2 were the target of this study. The mean operative time was 103±11 min. Early minor postoperative complications were detected in 18 patients (64%) and included nausea, vomiting and sialorrhea. Postoperative reflux esophagitis was detected in 2 patients (7%). Postoperative % EWL (excess weight loss) was 32.2% at 1 month, 48.9% at 3 months, 53.3% at 6 months, 66.7% at 12 months and 70.2% at 15 months. The improvement of the pre-existent co-morbidities occurred in 7 patients (53.8%). Conclusions: SSGS is a promising low cost restrictive bariatric operation. It is reversible and effective weight losing procedure in the short term.